2016 American Control Conference (ACC) 2016
DOI: 10.1109/acc.2016.7524965
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel testing of wake control strategies

Abstract: Goal of this paper is to present results from wind tunnel tests aimed at evaluating the potential of different wake control strategies for wind farm power maximization and load reduction. The experiments are conducted in a large boundary layer wind tunnel, using up to six servo-actuated and highly sensorized wind turbine scaled models in different wind farm layouts. Two main strategies are considered: the first derates the upstream wind turbines, while the second aims at redirecting wakes away from the downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 7 publications
4
103
0
Order By: Relevance
“…Wind tunnel tests have been conducted that show encouraging results that match simulation results based on wake redirection (Campagnolo et al (2016); Schottler et al (2016)). In addition, there are preliminary results of the benefits of wake steering from an offshore commercial wind farm (Fleming et al (2017c)).…”
Section: Introductionmentioning
confidence: 61%
“…Wind tunnel tests have been conducted that show encouraging results that match simulation results based on wake redirection (Campagnolo et al (2016); Schottler et al (2016)). In addition, there are preliminary results of the benefits of wake steering from an offshore commercial wind farm (Fleming et al (2017c)).…”
Section: Introductionmentioning
confidence: 61%
“…However, simple static induction control failed to increase wind-farm power, indicating the need for more involved induction control strategies. In addition, recent wind tunnel studies have indicated discrepancies between power gains predicted by engineering models and those observed in the wind tunnel, and have reported no significant power gains beyond measurement uncertainties for static axial induction control [9,10]. Furthermore, it is important to note that most of the studies on wind-farm control are performed in worst-case conditions, i.e., in which neighboring turbines are aligned with the mean wind direction, with maximal wake interaction and potential for coordinated control.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, control strategies at the farm level allow the wake interaction to be influenced and promise to improve overall wind-farm performance by improving wind conditions for downstream turbines. This can be achieved by redirecting propagating wakes (yaw control; see, e.g., Fleming et al, 2014;Gebraad et al, 2016;Campagnolo et al, 2016) or by affecting the induced wake velocity deficits (axial induction control; see, e.g., Nilsson et al, 2015;Annoni et al, 2016;Bartl and Saetran, 2016). A more exhaustive survey of wind-farm control in a broader context can be found in Knudsen et al (2015) and Boersma et al (2017).…”
Section: Introductionmentioning
confidence: 99%